CryoSat ocean product quality status and future evolution. Issue 6 (15th September 2018) - Bouffard, Jerome; Naeije, Marc; Banks, Christopher J.; Calafat, Francisco M.; Cipollini, Paolo; Snaith, Helen M.; Webb, Erica; Hall, Amanda; Mannan, Rubinder; Féménias, Pierre; Parrinello, Tommaso
Abstract: The main objectives of this paper are to present the status of the CryoSat ocean products and to give an overview of all associated quality control and validation activities. Launched in 2010, the polar-orbiting European Space Agency's (ESA) CryoSat mission was primarily developed to measure changes in the thickness of polar sea ice and elevation of the ice sheets. Going beyond its ice-monitoring objective, CryoSat is also a valuable source of data for the oceanographic community. The satellite's radar altimeter can measure high-resolution geophysical parameters from the open ocean to the coast. To enable their full scientific and operational exploitation, the ocean products continuously evolve and need to be quality-controlled and thoroughly validated via science-oriented diagnostics based on multi-platform in situ data, models and other satellite missions. In support to ESA, the CryoSat ocean validation teams conduct this quality assessment for both the near real time and offline ocean products, both over short time scales (daily and monthly monitoring) and long-term stability (annual trends). Based on the outcomes from these quality analyses and feedback from scientific oceanographic community, ESA intends to upgrade the CryoSat Ocean processing chain for Autumn 2017.